Biomimetic and estrogenic fibers promote tissue repair in mice and human skin via estrogen receptor β. (October 2020) - Ahn, Seungkuk; Chantre, Christophe O.; Ardoña, Herdeline Ann M.; Gonzalez, Grant M.; Campbell, Patrick H.; Parker, Kevin Kit
Abstract: The dynamic changes in estrogen levels throughout aging and during the menstrual cycle influence wound healing. Elevated estrogen levels during the pre-ovulation phase accelerate tissue repair, whereas reduced estrogen levels in post-menopausal women lead to slow healing. Although previous reports have shown that estrogen may potentiate healing by triggering the estrogen receptor (ER)-β signaling pathway, its binding to ER-α has been associated with severe collateral effects and has therefore limited its use as a therapeutic agent. To this end, soy phytoestrogens, which preferentially bind to the ER-β, are currently being explored as a safer therapeutic alternative to estrogen. However, the development and evaluation of phytoestrogen-based materials as local ER-β modulators remains largely unexplored. Here, we engineered biomimetic and estrogenic nanofiber wound dressings built from soy protein isolate (SPI) and hyaluronic acid (HA) using immersion rotary jet spinning. These engineered scaffolds were shown to successfully recapitulate the native dermal architecture, while delivering an ER-β-triggering phytoestrogen (genistein). When tested in ovariectomized mouse and ex vivo human skin tissues, HA/SPI scaffolds outperformed controls (no treatment or HA only scaffolds) towards promoting cutaneous tissue repair. These improved healing outcomes were prevented when the ER-β pathway was genetically or chemically inhibited. Our findings suggest that estrogenic fibrous scaffolds facilitate skin repair by ER-β activation.